RESEARCH OF TRANSVERSE GLUING OG LIGTHINDASTRY PARTS WITH POLIMERIC MATERIALS - HORIASHCHENKO, Serhiy; HOLINKA, Ievgeniia; DRAPAK, Georhiy; HORIASHCHENKO, kostyantun; POLISHCHUK, Oleg (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The paper presents the results of research on the preliminary gluing of parts of light industry, namely parts made of leather and artificial leather into a package. Zonal application of polymer adhesive material and a defined strength value for different types of packages are proposed. The relative displacement of the parts will lead to a violation of the integrity of the package and the destruction of the adhesive bond between them. That is, any relative displacement of the parts must lead to the destruction of their previously set position and is considered unacceptable. Therefore, determining the strength of the adhesive fixation of parts, which keeps them in a given position and determines the main task of the research. The substance used as an adhesive must ensure the fixation of the details of the shoe upper in a short period of time. This time is necessary only for the formation and stitching of a package of parts and depends on the parameters of the technological process and the performance of the equipment. In our case, when a pair of shoe upper blanks must be formed in one minute. To accurately determine the strength of the adhesive interaction between two parts, it is proposed to use the method of shifting (tearing) the adhesive joint. It was taken into account that natural and artificial leather have front and back sides that differ from each other. Namely, the dorsal side has larger capillary radii and greater porosity than the front side. Polymer material for gluing – Desmocol – was also chosen for research. The obtained values made it possible to form a general characteristic of the strength of adhesive joints for this type of polymer material used as glue. The obtained data show that it is quite possible to use the proposed zonal application of polymer adhesive material to ensure the non-slip strength of pre-glued parts. The strength value is sufficient for the further transportation of parts of the light industry to the next technological position without displacement. This can be used for systems of automated assembly of shoe upper blanks, stitching, manipulation, etc.